Development of an effective asphaltene-derived adsorbent for wastewater treatment: Characterization and methyl orange removal study. Issue 1 (February 2023) - Eshraghian, Afrooz; Yu, Linlong; Achari, Gopal; Sundararaj, Uttandaraman
Abstract: Conversion of asphaltene, an undesirable and abundant waste from the petroleum industry, to value-added products can offer sustainability and economic benefit. In this study, asphaltene was acid-treated to become a low-cost and effective adsorbent for removing dye from wastewater. It was hypothesized that asphaltene functionalization with acids will change the surface properties of asphaltene, leading to improved adsorption capabilities. Through acid treatment, the surface area of asphaltenes was increased and oxygen or nitrogen functionalities were incorporated into their structure confirmed by Fourier-transform infrared spectroscopy (FTIR), elemental analysis, Scanning Electron Microscopy (SEM) images, and nitrogen adsorption-desorption isotherm. Batch adsorption experiments were conducted to evaluate the capacity of modified asphaltenes to remove methyl orange (MO) from aqueous solutions. The effect of asphaltene modification techniques, MO solution pH (3−11), asphaltene dosage (0.5–10.0 g/L), contact time, and experimental temperature (25–45 °C) were evaluated. The adsorption removal percentage of MO by modified asphaltene was about three times higher than that of non-modified asphaltene. Modified asphaltene had a maximum adsorption capacity of 7.9 mg/g at 25 °C and a solution pH of 3. Moreover, it is shown that Freundlich isotherm, pseudo-second-order, and intra-particle diffusion kinetic models describe the adsorption process very well. Finally, the regeneration of the asphaltene was achieved using ethanol, and the MO removal efficiency can still be as high as 64 % after 5 cycles (initial removal efficiency is 96 %). This study indicates that the modified asphaltene can be used as a low-cost adsorbent for treating wastewater containing dyes and other organic contaminants. Graphical Abstract: ga1 Highlights: Asphaltene waste was used as adsorbent to remove methyl orange from wastewater. Acid treatment of asphaltene increased its surface area and adsorption capability. Modified asphaltene had a maximum adsorption capacity of 7.9 mg/g at 25 °C. The regeneration of the asphaltene was achieved using ethanol. Isotherm and kinetic models were studied to describe the adsorption process.